Exploring the Relationship between MIS and Decision-Making Process at Al-Hussein Bin Talal University - Ali M. Al-Ghonmein; Khaldun G. Al-Moghrabi; Hamed A. Talhouni (International Journal of Engineering and Management Research, 2020)
This study aims to identify the role of management information systems (MIS) towards decision-making in Al-Hussein Bin Talal University (AHU). To accomplish the objective of the study, the following hypotheses were formulated: There are NO statistically significant differences between MIS and the effectiveness of the decision-making process (DMP) at AHU. There are NO statistically significant differences in the attitudes of employees at AHU on the role of MIS in the effectiveness of (DMP) due to their demographic variables (gender, age, marital status, job experience, and scientific qualification). The study followed the analytical descriptive approach, a questionnaire was designed to collect the data, it was distributed to a sample of (180) managerial and academic staff of decision-makers at AHU with a recovery rate of (89%). The most important results are: There is a statistically significant relationship between MIS and the decision-making process effectiveness in AHU, The results also showed there are statistically significant differences between the role of management information systems in making decisions due to the variables (age, job experience, and scientific qualification). While there are no statistically significant differences of (gender and marital status) variables, the study recommend the need to increase the support of senior management at AHU for users of information systems, the need to provide training and development programs for them and the need to increase attention to MIS through regular maintenance, continuous development, protection of information, and building an integrated electronic system at the level of all Jordanian universities that guarantees participation as well as safe and effective information exchange between them.